(untitled) (World of finance, 2023)
Introduction. An important element of the implementation of the concept of sustainable development in Ukraine and the concept of the development of the system of financial support in the field of health care is the modernization of the financial mechanism of medical institutions, the development of new models of financial activity in the context of ensuring their stability and sustainability. The purpose of the article is to study the main theoretical and methodological approaches to the analysis of the financial stability of health care institutions in the context of sustainable development. Methods. The set goal was achieved using general scientific, special and empirical methods of learning processes and phenomena. In particular, the methods of analysis and synthesis, comparison, and generalization are used to understand the sustainable development of society and the enterprise, the financial stability of health care institutions; scientific abstraction, structural-logical and tabular methods, structural-dynamic and coefficient analysis - to determine and analyze the financial stability of medical institutions. Results. The theoretical foundations and methodical approaches of the analysis of financial stability have been studied. The methodology was adapted to modern health care institutions that have acquired features of an entrepreneurial nature, an analysis of the medical institution was carried out, and indicators were calculated to determine the level of financial status. Conclussions. Therefore, the financial stability of communal non-profit institutions is the state of financial resources and their management, which ensures the balance of assets and liabilities in a changing external and internal environment and ensures constant solvency and investment attractiveness within the limits of an acceptable level of risk. Analysis of the financial stability of health care institutions allows us to assess their readiness to repay their debts, financial independence, trends in the level of this independence, the rationality of managing state and self-raised funds. The algorithm for determining financial stability includes the use of a balance sheet model of financial equilibrium, a three-component indicator, determination of the optimal degrees of coverage of sources of financial support for health care, and calculation of absolute and relative indicators.